Optimization and Prediction of Sucker Rod Pump Performance on Well X-1 in Field X in the Future - Mohammad Firdaus Sabaruddin; Ilman Muhammad Azmi; Callula Engrasia Fathoni Firdaus; Muhamad Reza Shahrazade (Journal of Earth Energy Science, Engineering, and Technology, 2019)
The performance of the sucker rod pump is influenced by the characteristics of the well and reservoir such as pressure, well productivity, physical properties of the fluid, depth and diameter of the well. Therefore, pumping pumps need to be designed and optimized taking into account these conditions. As time goes on production changes in physical properties occur in the reservoir such as a decrease in reservoir pressure and a decrease in well productivity. Changes in the physical properties of the reservoir will affect the performance of the sucker rod pump. The purpose of this study is to design a sucker rod pump at X-1 well and forecast production in the future. The flow rate determination is obtained from the point of intersection between the pump intake pressure curve and IPR curves both in the present and in the future. In this study the pump speed is set at 10 SPM. Based on this method it was found that the well can produce with a flow rate of 1132 bpd with an oil flow rate of 27 bpd. The stroke length for this condition is 304 inch. Over time the production is estimated to cause the pressure to decrease to 1010 psi in 2040. The decrease in reservoir pressure causes the reduction in the flow rate of sucker rod pump to 1046 bpd with an oil flow rate of 14.6 bopd. So that the magnitude of the reduction in the flow rate of liquid between 2019 and 2040 was 7.6%, while the decrease in the oil flow rate was 45.9%. If the speed is set at 10 SPM, the stroke length needs to be reduced with time. The stroke length was designed to be 304 inches in 3019 and reduced to 281 inches in 2040.